DNA Damage and Radiosensitivity in Blood Cells from Subjects Undergoing 45 Days of Isolation and Confinement: An Explorative Study - Feiveson, Alan H.; Krieger, Stephanie S.; von Scheven, Gudrun; Crucian, Brian E.; Bürkle, Alexander; Stahn, Alexander C.; Wu, Honglu; Moreno-Villanueva, María (Current issues in molecular biology, 2022)
The effect of confined and isolated experience on astronauts’ health is an important factor to consider for future space exploration missions. The more confined and isolated humans are, the more likely they are to develop negative behavioral or cognitive conditions such as a mood decline, sleep disorder, depression, fatigue and/or physiological problems associated with chronic stress. Molecular mediators of chronic stress, such as cytokines, stress hormones or reactive oxygen species (ROS) are known to induce cellular damage including damage to the DNA. In view of the growing evidence of chronic stress-induced DNA damage, we conducted an explorative study and measured DNA strand breaks in 20 healthy adults. The participants were grouped into five teams (missions). Each team was composed of four participants, who spent 45 days in isolation and confinement in NASA’s Human Exploration Research Analog (HERA). Endogenous DNA integrity, ex-vivo radiation-induced DNA damage and the rates of DNA repair were assessed every week. Our results show a high inter-individual variability as well as differences between the missions, which cannot be explained by inter-individual variability alone. The ages and sex of the participants did not appear to influence the results.